Is this the beginning of the end for retail websites? A professional perspective. (25th May 2021) - Ramos, Ricardo F.; Rita, Paulo; Moro, Sérgio
This paper expects to understand professionals' opinion concerning the impact of the increasing use of social media (SM) and commercial mobile applications (MA) instead of retail websites in their online strategy. Unstructured interviews with internet professionals were applied on the LinkedIn professional SM platform, and 127 professionals provided their perspective. Data were analysed using a text mining approach and the outcome revealed professionals' resistance to set SM in the centre of the online strategy and highlighted the preference of users to use search engines that, in turn, will lead them to a retail website.